Predictors of corporate survival in the US and Australia: an exploratory case study. Issue 3 (21st June 2018) - Purves, Nigel; Niblock, Scott J.
Abstract : Purpose: The purpose of this paper is to investigate the relationship of financial ratios and non-financial factors of successful and failed corporations in the USA. Specifically, the authors provide evidence on whether financial ratios and non-financial factors can be jointly included as indicators to improve the predictive capacity of organisational success or failure in different countries and sectors. Design/methodology/approach: The paper utilises a mixed method exploratory case study focussing on listed corporations in the US and Australian manufacturing, agriculture, finance and property sectors. Findings: The financial ratio findings demonstrate that (with the exception of the failed Australian manufacturing sector) the integrated multi-measure (IMM) ratio approach consistently provides a higher classification rate for the failed and successful groups than those provided by an individual measure. In all cases the IMM method scored higher for US companies (with the exception of the failed Australian property sector). The findings also show that irrespective of the country location or sector, non-financial factors such as board composition and managements' involvement in organisational strategy impact on a corporation's success or failure. Practical implications: The findings reveal that non-financial factors occur prior to financial ratios when attempting to predict organisational success or failure and the IMM approach enables a more thorough examination of the predictive ability of financial ratios for US and Australian organisations. This intuitively indicates that when combined with financial ratios, non-financial factors may be a useful predictor of corporate success or failure across countries and sectors. Originality/value: Sound internal processes and the identification of both financial ratios and non-financial factors can be utilised to improve the reliability of financial failure models, enable corrective and preventative steps to be implemented by management and potentially reduce the costs of failure for US and Australian organisations.